Analisis Nilai Pendidikan Dalam Tradisi Mabuug-Buugan Masyarakat Desa Adat Kedonganan Sebagai Penerapan Ajaran Tri Hita Karana - Chika Aristia Santi, Ni Putu; Nerawati, Ni Gusti Ayu Agung (Jayapangus Press, 2024)
The noble values ​​that guide Balinese people in carrying out religious activities reflect the philosophical richness contained in each tradition, which in turn makes a positive contribution to the harmonization of nature, society and belief in Ida Sang Hyang Widi Wasa. Religious traditions in Bali also reflect the religious, social and moral values ​​upheld by society. These values ​​are reflected in practices such as pilgrimages, traditional ceremonies and other religious rituals, which are not only part of cultural heritage, but also serve as a guide in living daily life. The aim of this research is to examine the existence of the mabuug-buugan tradition which has a unique form, function and educational value and is different from traditions in general so as to obtain a holistic understanding. Qualitative research method with an action approach and research results obtained based on the results of the study in the form of educational values ​​in the mabuung-buugan tradition, including the value of social education, the value of religious education, the value of aesthetic education as well as in the mabuug-buugan tradition as an application of the teachings of Tri Hita Karana and there is an environmental message traditional rituals, it can be concluded that the mabuug-buugan tradition is an implementation of human harmony with the environment and the ida sang hyang widhi wasa expressed in the mabuug-buugan tradition, besides that it is also to unite the local community and this tradition contains social values ​​both in terms of togetherness, control themselves who follow the tradition of mabuug-buugan.